The role of circulating extracellular vesicles in breast cancer classification and molecular subtyping. Issue 4 (12th May 2019) - Platko, Khrystyna; Haas‐Neill, Sandor; Aziz, Tariq; Al‐Nedawi, Khalid
Abstract: Currently, tumor biopsies are used for breast cancer molecular subtyping. Biopsies are associated with various pathological changes and are thought to contribute to the dissemination of tumor cells. Extracellular vesicles shed by tumor cells into circulation exhibit the molecular signature of the parent cells. Herein, we show that proteomic analysis of circulating EV can discriminate BC patients from healthy subjects and indicate stage of the disease. Also, we performed a correlation between the BC molecular subtype using plasma EV and immunohistochemistry of tumor biopsies. Circulating EV may represent a useful, non‐invasive tool to study the molecular makeup of BC tumors.